Lightweight biodegradable cotton/albumen board (CAB) for sustainable environment - Yusof, Yusliza; Ahmad, Zuraida; Sopyan, Iis (2010)
The depletion of petroleum resources coupled with environmental awareness have spurred effort to produce biodegradable materials from natural resources, which is stable during storage and can be safely disposed after their intended time of use. These materials also can form the basis for sustainable and ecoefficient products that often results in lightweight structures having high stiffness and tailored properties for specific applications. Thereby, main objective of this work is to develop biodegradable board materials from cotton fiber reinforced egg albumen composites. The investigation is about the effect of fibre content on the mechanical properties, and thermal stability of the CAB. The composites having 0%,toughness was observed with increasing fiber content, with the optimum performance was obtained for the fiber content of 10 %w/w. The results have shown that addition of the cotton fibre increased the tensile strength and impact resistance in the range of 0.7 to 10.773 MPa and 1.3 to 19.0 kJ/m2 respectively, than that of the pristine albumen. The thermal stability of the composites was characterized by thermogravimetry analysis. The morphological study by SEM has revealed that the wettability of cotton fibre and albumen matrix was good for the fibre loading of 10 % w/w.